The Effect of Self-Efficacy on Academic Resilience through Subjective Well-Being as a Mediator Variable in Public High School Students in Tarakan City - Saputri Sri Lestari; Nanang Erma Gunawan (FKIP - Universitas Riau, 2026)
High school students encounter increasing academic demands that require not only strong academic competence but also psychological resources to adapt and persist in learning. Self-efficacy has been recognized as an important predictor of academic resilience; however, the mediating role of subjective well-being in this relationship remains inconclusive. This study aimed to examine the direct effect of self-efficacy on academic resilience and to investigate whether subjective well-being mediates this relationship among senior high school students in Tarakan City. This study employed a quantitative explanatory design involving 367 senior high school students selected through purposive random sampling from a population of 4,422 students. Data were collected using validated self-efficacy, subjective well-being, and academic resilience scales and analyzed using path analysis and the Sobel test. The findings revealed that self-efficacy significantly predicted both subjective well-being and academic resilience, while subjective well-being also had a significant positive effect on academic resilience. However, subjective well-being did not significantly mediate the relationship between self-efficacy and academic resilience. These findings indicate that self-efficacy contributes directly to strengthening students' academic resilience, whereas subjective well-being functions as an independent psychological factor rather than a mediating mechanism. This study provides empirical evidence that can inform the development of school-based interventions aimed at enhancing students' resilience through the improvement of self-efficacy.